Casting a Long Shadow: Leader–Leader Relationship and Employee Citizenship Behavior. (February 2019) - Muldoon, Jeffrey; Singh, Satvir; Vidyarthi, Prajya R.
This study examines the process and context of the relationship between leader–leader exchange (LLX) and subordinate organizational citizenship behavior (OCB) such that direct supervisors' attitudes and behaviors affect the relationship. Integrating social exchange theory with signaling theory, we argue that LLX influences the amount of OCBs that direct supervisors can obtain from subordinates and depends on direct supervisors' organizational-based self-esteem and support. In a sample of 290 direct supervisor/subordinate-dyads, using hierarchical linear modeling, we found that LLX partially mediates through supervisor support and is positively related to OCBs, and the mediation is highest in high organizational-based self-esteem.